Analysis of Conflict Potential in Religious Tourism Area: The Beji Antaboga Banyuwangi - Jeihany Anggrilla Safarani; Agus Adriyanto; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Beji Antaboga is a religious tourism area located on the slopes of Mount Raung, located in Genteng District, Banyuwangi Regency. This site describes the diversity of cultures and beliefs that are manifested as a form of multiculturalism. Initially, the development of the area was not free from conflict because it was only intended for Hindus. Then, deliberations were held so that the Beji Antaboga site, in an inclusive manner became a place of worship for various religions. This article shows that local people feel marginalized in managing the Beji Antaboga tourist area. Local people feel they are not involved, so they have limited knowledge about the structure of the Beji Antaboga management organization. Furthermore, local Muslim communities mostly carry out land clearing or development activities such as cooperation. Social jealousy over the gap in social structure can lead to open conflict. In conclusion, maintenance of the Beji Antaboga tourism area requires the participation of functional actors, such as the local government to build harmonization between parties and maintain peaceful conditions.